Diagnosis of Type 1 and Type 2 Myocardial Infarction Using a High-Sensitivity Cardiac Troponin I Assay with Sex-Specific 99th Percentiles Based on the Third Universal Definition of Myocardial Infarction Classification System. (6th January 2020) - Sandoval, Yader; Smith, Stephen W; Schulz, Karen M; Murakami, MaryAnn M; Love, Sara A; Nicholson, Jennifer; Apple, Fred S
Abstract: BACKGROUND: The frequency and characteristics of myocardial infarction (MI) subtypes per the Third Universal Definition of MI (TUDMI) classification system using high-sensitivity (hs) cardiac troponin assays with sex-specific cutoffs is not well known. We sought to describe the diagnostic characteristics of type 1 (T1MI) and type 2 (T2MI) MI using an hs–cardiac troponin I (hs-cTnI) assay with sex-specific cutoffs. METHODS: A total of 310 consecutive patients with serial cTnI measurements obtained on clinical indication were studied with contemporary and hs-cTnI assays. Ninety-ninth percentile sex-specific upper reference limits (URLs) for the hs-cTnI assay were 16 ng/L for females and 34 ng/L for males. The TUDMI consensus recommendations were used to define and adjudicate MI based on each URL. RESULTS: A total of 127 (41%) patients had at least 1 hs-cTnI exceeding the sex-specific 99th percentiles, whereas 183 (59%) had hs-cTnI within the reference interval. Females had more myocardial injury related to supply/demand ischemia than males (39% vs 18%, P = 0.01), whereas males had more multifactorial or indeterminate injury (52% vs 33%, P = 0.05). By hs-cTnI, there were 32 (10%) acute MIs, among which 10 (3%) were T1MI and 22 (7%) were T2MI. T2MI represented 69% (22 out of 32) of all acute MIs, whereas T1MI represented 31% (10 out of 32). Ninety-five patients (31%) had an increased hs-cTnI above the 99th percentile but did not meet criteria for acute MI. The most common triggers for T2MI were tachyarrhythmias, hypotension/shock, and hypertension. By contemporary cTnI, more MIs (14 T1MI and 29 T2MI) were diagnosed. By contemporary cTnI, there were 43 MIs, 14 T1MI, and 29 T2MI. CONCLUSIONS: Fewer MI diagnoses were found with the hs-cTnI assay, contrary to the commonly accepted idea that hs-cTnI will lead to excessive false-positive diagnoses.